2006
DOI: 10.1111/j.1528-1167.2006.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Pentobarbital Delivery Can Prevent Locally Induced Neocortical Seizures in Rats: The Prospect of Transmeningeal Pharmacotherapy for Intractable Focal Epilepsy

Abstract: Summary:Purpose: To determine whether epidural pentobarbital (PB) delivery can prevent and/or terminate neocortical seizures induced by locally administered acetylcholine (Ach) in freely moving rats.Methods: Rats were implanted permanently with an epidural cup placed over the right parietal cortex with intact dura mater. Epidural screw-electrodes, secured to the cup, recorded local neocortical EEG activity. In the seizure-termination study, Ach was delivered into the epidural cup, and after the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Since diffusible agents rapidly dissipate from the injection site, they must be infused continuously to obtain the sustained tissue concentrations necessary for chronic seizure protection. Antiseizure agents can also be applied to the brain surface via the epidural or subdural spaces, so that delivery occurs by the transmeningeal route 6-8. This mode of delivery, which is particularly applicable for neocortical epilepsies, requires therapeutic molecules that can penetrate the meninges and diffuse into the underlying neocortex to at least a limited extent.…”
Section: Introductionmentioning
confidence: 99%
“…Since diffusible agents rapidly dissipate from the injection site, they must be infused continuously to obtain the sustained tissue concentrations necessary for chronic seizure protection. Antiseizure agents can also be applied to the brain surface via the epidural or subdural spaces, so that delivery occurs by the transmeningeal route 6-8. This mode of delivery, which is particularly applicable for neocortical epilepsies, requires therapeutic molecules that can penetrate the meninges and diffuse into the underlying neocortex to at least a limited extent.…”
Section: Introductionmentioning
confidence: 99%
“…(This experiment also demonstrated the therapeutic effect of a single subarachnoid muscimol administration in stopping ongoing ACh-seizures (C, I) during saline treatment). [19][20][21] and intracerebral infusion of neurotrophic factors promotes neurogenesis after stroke [22], whereas clinically, localized postoperative chemotherapy is beneficial for glioma [23]. These and other studies of intracranial drug delivery have used pumps for convection-enhanced delivery (CED) via narrow-lumen intraparenchymal cannulae [21,[23][24][25], as well as drug-releasing polymers or micro-electro-mechanical-system (MEMS) microchips [26][27][28].…”
Section: Cortical Strokesmentioning
confidence: 98%
“…At least a subgroup of this patient population could benefit from localized pharmacodialysis treatment. Administration of antiepileptic drugs directly into the seizure focus has been proposed by many groups [19][20][21]24,26,27]. Complementing this pharmacotherapy through drainage of proconvulsant Fig.…”
Section: Pharmacodialysis Systems For Neurological and Psychiatric DImentioning
confidence: 99%
“…Thus, epidurally administered diazepam, pentobarbital and muscimol have been shown to prevent and/or terminate experimentally induced focal neocortical seizures in rats (Collins, 1980;Eder et al, 1997;Stein et al, 2000;Ludvig et al, 2006Ludvig et al, , 2009. Relevant autoradiographic and histological studies have demonstrated the actual intracortical diffusion and spread of water-soluble drugs, such as acetylcholine, N-methyl-D-aspartate and methylene blue (Cornblath and Ferguson, 1976;Ludvig et al, 2008).…”
Section: Supporting Experimental Datamentioning
confidence: 99%
“…Extensive studies have been devoted to explore the potential of this strategy for the treatment of focal neocortical epilepsy (Ludvig et al, 2006(Ludvig et al, , 2009(Ludvig et al, , 2010aMadhavan et al, 2008), but similar studies have yet to be conducted in the field of stroke research. The concept of subarachnoid pharmacotherapy for maximizing recovery after cortical ischemic stroke ( Fig.…”
Section: The Concept Of Subarachnoid Pharmacotherapy For Post-stroke mentioning
confidence: 99%